(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
The language that is used in commercial advertising serves the objective of convincing the general public of the merits and benefits of a product in the hopes that it will eventually be purchased by customers and placed on the market. Advertisers employ specific language in their discourse because there are advantages to using odd and disputed terminology in contrast to basic language, which is why basic language is avoided whenever possible. This is a deserving area for more research, especially in terms of how speaking actions are performed. An utterance is considered to be a speech act if it contains an action as a functional unit of communication and takes into account aspects of the speaking context. Speech acts may take several forms. When a person says anything, Austin (1962) asserts that they are also acting out that same thing. Speech actions may be categorized as representational, directive, commissive, expressive, or proclamation. The purpose of this study is to analyze the different types of speech movements that are used in television commercials. This study obtained its data from several advertisements for food and beverages, including those for Tango, Chips Lisa’s, ABC chili sauce, and Ads, amongst others. The qualitative research data were acquired using the methods of documenting and observing the phenomena of interest. In this particular piece of study that was conducted in 1996, the data was analyzed using Yule’s pragmatic theory. Informal presentations are made of the findings obtained from the data analysis. According to the results of the inquiry, it is possible to draw the conclusion that commercial advertising often makes use of the following four types of speech acts: representational, directive, expressive, and commissive.